Ending campus violence: A cross-sectional study among undergraduates to assess the silence majority in a lower resource setting - Fazla Fayaz; Irosha Nilaweera; Riyas Cassim; Dulani Samaranayake (Social Sciences and Humanities Open, 2023)
The objective is to assess the prevalence and association of Dismissive-Attitude-towards-Violence(DAV) among second-year undergraduates in a lower-resource-setting. A descriptive-cross-sectional-study was carried out among 1290, second-year undergraduates in Sri Lanka using multi-stage-stratified cluster-sampling. Four universities were randomly selected from ten. Undergraduates from foreign-countries, those following external-degrees, distance-learning, clergymen, undergraduates of medical and allied-health were excluded. The cluster size was 30 and 43 clusters were allocated proportionately to the total second-year undergraduate population in each university and faculty. In each faculty, clusters were proportionately allocated to general-degree programmes with more than 100 students. DAV was measured using three items locally validated, scoring from 0 for “more than 5 times” and 4 for “never” and provided a minimum score of 0 to a maximum possible score of 12. The minimum threshold score for the presence of DAV was seven. Response-rate for the study was 88.1% (n = 1136). The prevalence of DAV was 82.2% (95%CI:79.9%–84.4%) which was significantly associated with poor relationships with teachers, friends, lecturers, batchmates and seniors, having peers with high-delinquency-behaviour, participating in ragging and involving in politics. DAV is negatively associated with emotional-intelligence. Accepting violent behaviour is a huge problem among undergraduates, which was influenced by many university and relationship-related factors. Therefore, creating healthy relationships in various levels, improving emotional intelligence and introducing other ways to recognize seniority among students should be supported and institutionalized to end campus violence.